ANALISIS STRATEGI PENGELOLAAN KOPERASI SIMPAN PINJAM DI KOPERASI LKM SYARIAH UKHUWAH BINTANG INSANI - Wardonsoni Wardonsoni; Gustiya Sunarti; Fatimah Yunus (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
This study aims to analyze the management strategy of savings and loan cooperatives at the Ukhuwah Bintang Insani Islamic Microfinance Cooperative (LKM Syariah), a microfinance institution operating based on sharia principles. This study focuses on four main aspects: planning, organization, implementation, and supervision, which are applied to support the effectiveness of operational activities. The research method used is descriptive qualitative through in-depth interviews, direct observation, and review of various organizational documents. The results show that the cooperative has implemented a targeted management strategy oriented towards member empowerment, improving service quality, and complying with sharia. However, several challenges remain, such as limited human resources, suboptimal technology utilization, and the need to strengthen the internal control system. The findings of this study emphasize the importance of increasing institutional capacity and professionalism of cooperative managers so that cooperatives can adapt to changing member needs and the dynamics of the business environment. This research provides an empirical contribution to the strategy for developing sustainable management of sharia cooperatives.